Celebrating the 5-year anniversary of Fresno State's baseball national championship - Hughes, Eddie::::::::: (2013)
Five years ago today, a historic 'Bulldog' pile in Omaha, Neb., capped one of the most remarkable achievements in the history of collegiate athletics as Fresno State won the 2008 NCAA Division I Baseball Championship with a 6-1 victory over Georgia at Rosenblatt Stadium.